Algebra Hyperstructure Concept and Its Application on Oxidation Reduction: Actinium (Ac) and Berkelium (Bk) - Huwae, Elsa; Patty, Henry Willyam Michel; Rahakbauw, Dorteus L; Dahoklory, Novita (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2024)
The concept of algebraic hyperstructure is a generalization of the concept of algebraic structure. The algebraic hyperstructure concepts discussed in this research include hypergroups, semihypergroups, and -group and it is known that this concept has application in the field of science, one of which in the field of chemistry, namely redox reactions. The aim of this research is to discuss the concept of algebraic hyperstructures and its application in redox reactions of the elements actinium and berkelium . In this research, the redox reactions of the elements actinium and berkelium were obtained and the results of the redox reactions of these two elements formed a semihypergroups and -semigroups.